Identification of molecular target of diallyl trisulfide in leukemic cells. Issue 8 (3rd August 2014) - Suda, Shun; Watanabe, Kazunari; Tanaka, Yuki; Watanabe, Kazuhiro; Tanaka, Rie; Ogihara, Jun; Ariga, Toyohiko; Hosono-Fukao, Tomomi; Hosono, Takashi; Seki, Taiichiro
Abstract: To identify the molecular target of diallyl trisulfide (DATS) in human leukemic cell line U937, we examined modification of thiol group(s) of cellular proteins by the redox 2D PAGE. A unique protein spot appeared by DATS treatment was identified to be heat shock protein 27 (HSP27). Hsp27 is suggested to be one of the molecular target of DATS in U937.